2010
DOI: 10.1111/j.1365-2885.2010.01220.x
|View full text |Cite
|
Sign up to set email alerts
|

Influence of a pig respiratory disease on the pharmacokinetic behaviour of amoxicillin after oral ad libitum administration in medicated feed

Abstract: The pharmacokinetic properties of amoxicillin in healthy and respiratory-diseased pigs were studied, after ad libitum administration of medicated feed. In addition, amoxicillin dose linearity and drug penetration into respiratory tract tissues were evaluated in diseased animals. The respiratory disease involves porcine reproductive and respiratory syndrome virus and bacterial agents such as Pasteurella multocida, Bordetella bronchiseptica and Streptococcus suis. Typical clinical signs and gross lesions of resp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
17
1
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(20 citation statements)
references
References 58 publications
(68 reference statements)
1
17
1
1
Order By: Relevance
“…For the WDT of ENR, our findings in pigs were 5 days, which was similar to 5 or 6 days in poultry in previous reports (San Martin et al, 2010; Terrado-Campos et al, 2017). The previous studies revealed that after exposure to ENR at a dose of 10 mg/kg, the WDT was 5, 7, and 10 days in pigs (Delsol et al, 2004; San et al, 2007; Liu et al, 2011), and 23 days in piaractus mesopotamicus (Luo et al, 2010), most of which was far longer than that in our study (Wiuff et al, 2002; San et al, 2007; Godoy et al, 2011; Paschoal et al, 2013). Therefore, EEG had an advantage with a short WDT.…”
Section: Discussioncontrasting
confidence: 44%
See 1 more Smart Citation
“…For the WDT of ENR, our findings in pigs were 5 days, which was similar to 5 or 6 days in poultry in previous reports (San Martin et al, 2010; Terrado-Campos et al, 2017). The previous studies revealed that after exposure to ENR at a dose of 10 mg/kg, the WDT was 5, 7, and 10 days in pigs (Delsol et al, 2004; San et al, 2007; Liu et al, 2011), and 23 days in piaractus mesopotamicus (Luo et al, 2010), most of which was far longer than that in our study (Wiuff et al, 2002; San et al, 2007; Godoy et al, 2011; Paschoal et al, 2013). Therefore, EEG had an advantage with a short WDT.…”
Section: Discussioncontrasting
confidence: 44%
“…Previous reports had established a close link between the respiratory disease risk and the productivity decrease in animals (Godoy et al, 2011; Paschoal et al, 2013; Hassanpouraghdam et al, 2015; Sala et al, 2015). Generally, the strain with MIC 95 or MIC 90 was the preference for establishment of infection model and indicators for clinical treatment.…”
Section: Discussionmentioning
confidence: 88%
“…Godoy et al. () also confirmed amoxicillin plasma concentrations were also higher in respiratory disease affected pigs after oral administration of amoxicillin. This suggests that the PK results in healthy pigs might underestimate the plasma concentrations and the time above MICs achieved and thereby a better treatment effect might be seen.…”
Section: Clinical Data and Field Experiencesmentioning
confidence: 81%
“…A study on pigs showed that with the same amoxicillin dose serum amoxicillin levels were significantly lower in healthy pigs than in diseased animals suffering from a respiratory infection. 33 Organ cultures lack the impact of infection-related factors, which may potentiate the effects of chemical compounds. Thus the effect of a single factor, here NaF or amoxicillin, may be weak unless high exposure concentrations are used.…”
Section: Discussionmentioning
confidence: 99%